A Skin‐Like Pressure‐ and Vibration‐Sensitive Tactile Sensor Based on Polyacrylamide/Silk Fibroin Elastomer. (5th February 2022) - Li, Shengyou; Liu, Guoqing; Wen, Hao; Liu, Guoyi; Wang, Hao; Ye, Meidan; Yang, Yun; Guo, Wenxi; Liu, Yufei
Abstract: With bio‐integrated electronics booming, stretchable, elastic, compliance, and biocompatible elastomers attract immense research interest due to their potential to integrate with electronic devices and soft tissues. In this work, a double network skin‐like elastomer based on hydrophobic‐polyacrylamide/silk fibroin (HSF) is synthesized. The addition of the fibroin in polyacrylamide hydrogel significantly improves its stretchability, resilience, and tear resistance. Specifically, the HSF elastomer demonstrates a tensile strain as high as 1000% with the corresponding tensile stress of 0.27 MPa and great resilience (550 cycles). Based on such HSF, a hybrid mechanoreceptor sensor is fabricated, which can simultaneously implement slow adaptive and fast adaptive pulses like human skin. This device realizes the detection of a variety of human movements such as joint movement, vocalization, or pulse and high‐frequency vibration signal recognition, which demonstrates its potential applications in bio‐integrated electronics. Abstract : To mimic real human skin, a double network hydrogel is synthesized based on hydrophobic‐polyacrylamide/silk fibroin (HSF), which exhibits skin‐like mechanical properties (stretchability, resilience, and tear resistance). Based on the HSF, a hybrid mechanoreceptor sensor is fabricated, which can simultaneously implement slow adaptive and fast adaptive pulses like human skin.